2013
DOI: 10.1128/aac.01965-12
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Discontinuation of Empiric Vancomycin Therapy in Patients with Suspected Methicillin-Resistant Staphylococcus aureus Health Care-Associated Pneumonia

Abstract: f Healthcare-associated pneumonia (HCAP) guidelines recommend de-escalating initial antibiotic therapy based on results from lower-respiratory-tract cultures. In the absence of adequate lower respiratory cultures, physicians are sometimes reluctant to discontinue empirical vancomycin, which is given for suspected methicillin-resistant Staphylococcus aureus (MRSA) HCAP. We evaluated a strategy of discontinuing vancomycin if both nasal and throat cultures were negative for MRSA when lower-respiratory-tract cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 44 publications
0
24
0
2
Order By: Relevance
“…Some interventions to increase the appropriateness of continued empirical vancomycin use at 72 to 96 h would be sensible and helpful in reducing the amount of vancomycin prescribed, considering that inappropriately continued vancomycin use makes up one-quarter of the vancomycin prescribed. The safety of vancomycin discontinuation in the absence of documented MRSA has been suggested by multiple studies (26,27), and Hamilton et al showed that a continuation form at 72 h was effective in reducing inappropriately continued vancomycin use (24). In cases of suspected ventilator-associated pneumonia, antibiotic discontinuation strategies based on clinical criteria were successful in safely reducing antibiotic treatment duration (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Some interventions to increase the appropriateness of continued empirical vancomycin use at 72 to 96 h would be sensible and helpful in reducing the amount of vancomycin prescribed, considering that inappropriately continued vancomycin use makes up one-quarter of the vancomycin prescribed. The safety of vancomycin discontinuation in the absence of documented MRSA has been suggested by multiple studies (26,27), and Hamilton et al showed that a continuation form at 72 h was effective in reducing inappropriately continued vancomycin use (24). In cases of suspected ventilator-associated pneumonia, antibiotic discontinuation strategies based on clinical criteria were successful in safely reducing antibiotic treatment duration (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of MRSA screening tests to guide antibiotic therapy remains poorly studied. Prior studies have evaluated their use in multiple situations, including intra-abdominal (10), postoperative (11), respiratory (12,13), and overall documented clinical infections (14). There is little published on the use of MRSA screening in bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged broad-spectrum empiric therapy can also contribute to the selection and spread of multidrug resistant organisms (MDROs) (16,17). Rapid deescalation to optimal therapy based on resistance testing (11,18,19) is therefore important for antimicrobial stewardship.…”
mentioning
confidence: 99%